A new distal radius fracture classification depending on the specific fragments through machine learning clustering method - Yuling Gao; Yanrui Zhao; Yang Liu; Shan Lei; Hanzhou Wang; Yuerong Lizhu; Tianchao Lu; Zhexian Cheng; Dong Wang; Binzhi Zhao; Ziyi Li; Junlin Zhou (BMC Musculoskeletal Disorders)
Abstract Purposes The objective of this study was to investigate intra-articular distal radius fractures, aiming to provide a comprehensive analysis of fracture patterns and discuss the corresponding treatment strategies for each pattern. Methods 294 cases of intra-articular distal radius fractures lines were collected and clustered thorough K-means and hierarchical clustering algorithm. The demographic data of patients and the clinical treatment outcomes were recorded. For functional evaluation, quick Disabilities of the Arm, Shoulder, and Hand (DASH) score, visual analog scale (VAS) pain score, range of motion (ROM) of the wrist joint and the percentage of the grip strength relative to the healthy wrist at 12 months follow-up were evaluated and recorded; For radiographic parameters of volar tilt (VT), radial inclination (RI), and ulnar variance (UV) were obtained; The occurrence of complications was carefully assessed and documented. Results Totally 294 patients were included and divided into the volar side affected group and the dorsal side affected groups. And each group was further categorized into three types: type I, with two parts fractures with either one volar/dorsal side intact; type II, with three parts fractures with  volar/dorsal side simply affected; and type III, with four parts fractures with volar/dorsal side communited affected. The volar plate fixation was performed as the standard treatment, while the combined plate fixation was used for comminuted dorsal bone defects of the metaphysis and impaction. There were no differences in the postoperative radiograph parameters, functional outcomes and incidences of complications for each type of volar side group and dorsal side group except that the 3.2 type DRFs showed less range of flexion (75.56±7.48)° and extension (61.65±9.9)° than other dorsal types. Conclusions A new intra-articular distal radius fractures classification was proposed based on the affection condition of volar or dorsal side. The volar plate fixation is an effective treatment for the intra-articular distal radius fractures, while combined plate fixation can be considered as an alternative treatment for dorsal side comminuted fractures. Level of evidence III a